PEMANFAATAN NANAS (Ananas comosus L.) SUBGRADE SEBAGAI FRUIT LEATHER NANAS GUNA MENDUKUNG PENGEMBANGAN AGROINDUSTRI DI KEDIRI: KAJIAN PENAMBAHAN KARAGINAN DAN SORBITOL - Arie Febrianto Mulyadi; Susinggih Wijana; Laylatul Laurieka Fajrin (Faculty of Agricultural Technology, University of Jember, 2015)
Subgrade Pineapple fruit are perishable fruit. For alternative in maintaining this subgrade pineapple condition is to do processing into products fruit leather. The choosen product is fruit leather that is to handle the pineapple short shelf life, and enhance the value of selling pineapple subgrade. At issue was a product of fruit leather on the market have the inherent weakness of the texture is hard and sour flavors, so it needs to be fixed by addition of sorbitol and carrageenan with the best composition for producing leather by the best organoleptic quality. This research was conducted by RAK (randomized block design), using two treatment factors are carrageenan concentration of 0.2%, 0.4%, and 0.6%, and 4% and sorbitol, 6%, and 8%. Based on the results of organoleptik test, the value of panelist for taste, and texture significantly (α = 5%), while the value of panelist on the aroma and the color was not significant (α = 5%). The best treatment selection, taken from the highest value in the addition of carrageenan concentration of 0.2% with the addition of sorbitol by 8% with moisture content of 3.57%, with a total acid of 0.7% and total sugar by 95%.Keywords: carrageenan, leather, organoleptik, sorbitol, subgrade pineapple